Practices of Civil-Military Relations in Complex Peace Operations: Comparative Case Study of US and Canada Provincial Reconstruction Teams in Afghanistan - Grant, Laura (Université d'Ottawa / University of Ottawa, 2021)
Traditional analyses of operational effectiveness often lack consideration of civil-military relations. However, in operations with complex and ambitious political aims, such as democratization, stabilization and reconstruction, economic development, and respect for human rights, taking a comprehensive approach (the co-ordination of military, diplomatic, and development efforts) is essential. The creation of the Provincial Reconstruction Teams (PRTs) in Afghanistan aimed to essentially operationalize the comprehensive approach but was largely viewed as ineffective. The aim of this thesis is to increase the understanding of why the comprehensive approach in PRTs failed to live up to its potential and increase operational effectiveness through a comparative case study of US and Canada PRTs. As often is the case with complex peace operations, the mandates given to both military and civilian leaders are usually broad with little detail and thus are open for interpretation. As such, leadership has significant leeway as to how to conduct the operation, and many leaders have different ways of doing everyday things based on their own dispositions. The current theorizing of civil-military relations largely relies on rationalist and positivist assumptions which cannot readily capture the everyday experiences and dispositions of interveners and are less than insightful when it comes to describing and explaining the nuances of civil-military relations. By using a practice theory lens (specifically Bourdieu’s concepts of habitus, field, capital, and hysteresis), allows one to move away from models of actions based on realist assumptions and analyze civil-military relations as the result of different processes, practices, and systems of knowledge. The principal argument of this thesis is that because the habitus of the US and Canada were so misaligned with the field, actual operationalization (or embodiment) of the comprehensive approach was very sporadic and was largely dependent on leadership personality, which negatively effected effectiveness. Without understanding the systems of knowledge and sense-making (the habitus) that underlie decision-making processes one cannot assume that leadership will change its everyday practices to better embody the comprehensive approach. Without this understanding, it is necessary to put in place standard practices, such as training and clearer mandates, to help mitigate hysteresis (or the lag between generating practices that are in line with the new conditions).
Keywords: Afghanistan; civil-military relations; practice theory; effectiveness